2018
DOI: 10.1038/s41598-018-25061-z
|View full text |Cite
|
Sign up to set email alerts
|

In silico assessment of the conduction mechanism of the Ryanodine Receptor 1 reveals previously unknown exit pathways

Abstract: The ryanodine receptor 1 is a large calcium ion channel found in mammalian skeletal muscle. The ion channel gained a lot of attention recently, after multiple independent authors published near-atomic cryo electron microscopy data. Taking advantage of the unprecedented quality of structural data, we performed molecular dynamics simulations on the entire ion channel as well as on a reduced model. We calculated potentials of mean force for Ba2+, Ca2+, Mg2+, K+, Na+ and Cl− ions using umbrella sampling to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 101 publications
5
18
0
Order By: Relevance
“…By calculating the residence time of carboxylate oxygen of negatively charged residues within a sphere with a radius of 5 Å around the binding site L, we identified that the binding site L is formed by the interaction of Ca 2+ ions with D4899, E4900, and D4903 residues ( Fig. 3b), which agrees well with previous experimental and computational studies 28,30 . The large probability of finding Ca 2+ in the selectivity filter also indicates that the Ca 2+ can easily accumulate around the luminal vestibule and move into the upper filter, and the rate-determining step of permeation is the process of passing through the lower selectivity filter or gate constrictions.…”
Section: The Ca 2+ Binding Sites In the Pore Regionsupporting
confidence: 88%
See 3 more Smart Citations
“…By calculating the residence time of carboxylate oxygen of negatively charged residues within a sphere with a radius of 5 Å around the binding site L, we identified that the binding site L is formed by the interaction of Ca 2+ ions with D4899, E4900, and D4903 residues ( Fig. 3b), which agrees well with previous experimental and computational studies 28,30 . The large probability of finding Ca 2+ in the selectivity filter also indicates that the Ca 2+ can easily accumulate around the luminal vestibule and move into the upper filter, and the rate-determining step of permeation is the process of passing through the lower selectivity filter or gate constrictions.…”
Section: The Ca 2+ Binding Sites In the Pore Regionsupporting
confidence: 88%
“…2c). Since the channel is in its open state, this indicated that the default Ca 2+ model gave us qualitatively wrong simulation results here, as also observed by another recent study 28 . A close inspection of the MD trajectories showed that the Ca 2+ ions were tightly bound to the protein, again confirming that the binding affinity between Ca 2+ and protein is too strong with the conventional Ca 2+ model.…”
Section: The Permeability Of the Open-state Ryr1supporting
confidence: 72%
See 2 more Smart Citations
“…Many variants within the CS plane of interest occur at positions that are exposed to solution, often in open cavities, suggesting these cavities have important roles in channel function. Indeed, recent biophysical simulation studies have revealed additional ion conduction pathways that permeate the lateral aspect of the RyR1 CS and may thereby enable lateral Ca 2+ efflux into the cytoplasm [22]. …”
Section: Discussionmentioning
confidence: 99%